Você está na página 1de 22

M(x)

a i

{Φ i } i=0

M(x) =

i=0

a i Φ i (x).

[a, b], w(x)

Φ n ; Φ m = b Φ n (xm (x)w(x)dx = δ nm ,

a

δ nm = 0

1

n

i = j.

= m,

M

R

−∞ ≤ a b ≤ ∞ [a, b] α(x)

α(x) : [a, b] R α

(a, b)

µ k = b x k (x),

a

k = 0, 1, 2, · · · .

µ k (x)

(a, b)

w : (a, b) R w (x) =

w(x)dx x (a, b) w(x)dx 0 (a, b)

w

P n

n

P n = span{x k : k = 0, 1, ··· , n}.

P n n

P n (x)

P n (x) = a 0 + a 1 x +

+

a n x n =

n

k=0

a k x k , a n = 0.

P n (x) P n {P n (x)}

w(x) (a, b)

n=0

P n ; P m = b P n (x)P m (x)w(x)dx = 0, n

a

= m.

x

P n (x) ; P m (x) =

M

i=1

P n (x i )P m (x i )ω(x i ).

ω(x)

a b

M

P 0 (x), P 1 (x), ··· , P j (x)

n x

{1, x, x 2 , x 3 , x 4 ,

,

x n },

P 0 (x), P 1 (x), P 2 (x),

, P n (x)

P 0 (x) = 1,

n = 1, 2, 3, · · · ,

P n (x) = x n + α 0 P 0 (x) + α 1 P 1 (x) + ··· + α n1 P n1 (x),

α i

α k = P x k k ; ; P P k k , k = 0, 1, 2, ··· , n 1.

{P n (x)} n=0

P n ; P m = 0

1

n

n = m.

= m,

{P

n

(x)}

n=1

P 0 (x), P 1 (x), ··· , P n (x)

n

{P k (x)} k=0

P n P n

P n x k k = 1, · · · , n P k (x), k = 0, 1, 2, · · · , n P k (x) P n P n w(x) [a, b]

{P n (x)} n=0 {Q n (x)} n=0 w(x) [a, b]

P n (x) = c n Q n (x),

c n R , n N

P n (x) {P n (x)} n=0

P n (x)

= P n (x) ; P n (x) .

{P

n

(x)} n=1

n

P

(x)

=

P n (x)

P n (x) .

{P n (x)} (a, b) w(x)

n=0

P n+1 (x) = (α n x β n )P n (x) γ n P n1 (x), n

P 1 (x) = 0,

P 0 (x) = a 0 .

0,

α n , β n γ n n 0,

α n = a n

a n1

= 0;

β n = γ n

xP n ; P n

P n ; P n ,

γ n =

γ n

P n ; P n

γ

n1

P n1 ; P n1

= 0.

P n (x) n=0 {P n (x)}

w(x) P n

¯

n=0

P n (x) = P n (x) , n 1.

¯

a n

{P n (x)}

{P n (x)} n=0

(a, b) w(x)

¯

P n (x) = (x β n ) P n (x) γ n P n1 (x),

¯

¯

¯ ¯

P 1 (x) = 0, P 0 (x) = 1 β n , γ n n 1,

β n = x

¯

P n ;

P n ;

P n

¯

¯

P n ,

¯

γ n =

¯

P n ;

P n

¯

P ¯ n1 ; P n1

¯

= 0.

P n (x) P n (x) (a, b)

w(x) P n (x)

(a, b)

x 0 = a, x n+1 = b x 1 < x 2 <

··· < x n P n P n+1

(x j , x j+1 ) , j = 0, 1, · · · , n.

{x i } i=0 n P n+1 (x)

J n+1 =

δ

0

1

δ

1

1

n1

2

δ n1

n

n

δ n

δ j = β j j ,

α j , β j , γ j

α

j 0;

j =

α j1 α j1 γ j

1

α

j

,

j 1.

J n+1 =

β 0

 

γ

1

γ 1

β 1

γ n1

γ 2

β n1

γ n

γ n

β n

β j γ j

W n+1 W = diag(λ 1 , λ 2 , ··· , λ n+1 ) W

W W W = I n + 1 × n + 1

x j = λ j .

a x b

,

2 [1, 1] ω(x) =

1

{Le n (x)}, n = 0, 1, 2,

Le n+1 (x) = 2n + 1 xLe n (x) n + 1 Le n1 (x); n

n + 1

n

> 0,

Le 0 (x) = 1 Le 1 (x) = x,

a n =

(2n)!

2 n (n!) 2 .

Le n

1

Le n , Le m 1 Le n (x)Le m (x)dx

2

2n+1 δ nm .

Le 0 = 1

Le 1 = x

Le 2 =

1

2 (3x 2 1)

Le 3 =

Le 4 = 1 8 (35x 4 30x 2 + 3)

Le 5 = 1 8 (63x 5 70x 3 + 15x)

Le 6 =

2 (5x 3 3x)

1

16 1 (231x 6 315x 4 + 105x 2 5)

6 1 (231 x 6 − 315 x 4 + 105 x 2 − 5) ¯

¯

¯

Le n+1 (x) = (x 0) Le n (x)

β n = 0 γ n =

1

4n 2 .

n

2

4n 2 1

¯

Le n1 (x),

La n (x), n = 0, 1, 2,

L 2 [0, ] ω(x) = exp(x)

La 0 (x) = 1

La 1 (x) = 1 x

La n+1 (x) = (2n + 1 x) n + 1

La n (x) nLa n1 (x),

a n = (1) (n!)

n

.

La n

La n , La m =

La n (x)La m (x) exp(x)dx = δ nm .

0

La 0 = 1

La 2 =

La 3 =

24 (x 4 16x 3 + 72x 2 96x + 24

La 1 = 1 x

1

2 (x 2 4x + 2)

1 6 (x 3 + 9x 2 18x + 6

1

La 4 =

1

120 (x 5 + 25x 4 200x 3 + 600x + 120)

La 5 =

1

720 (x 6 36x 5 + 450x 4 2400x 3 + 5400x 2 4320x + 720)

La 6 =

2400 x 3 + 5400 x 2 − 4320 x + 720) La 6 = La

La n (x) = La n (x)·n!

(1) n

¯

¯

¯

La n+1 (x) = (x (2n + 1)) La n (x) n La n1 (x),

β n = 2n + 1 γ n = n 2

H n (x)

ω(x) =

1

π exp (x 2 ) ,

x

H n+1 (x) = 2xH n (x) 2nH n1 (x),

H 0 (x) = 1 H 1 (x) = 2x

H n

a n = 2 n .

h n H n , H n

π

1

[H n (x)] 2 exp (x 2 ) dx 2 n n!

H 0 = 1

H 1 = 2x

H 3 = 8x 3 12x

H 4 = 16x 4 48x 2 + 12

H 5 = 32x 5 160x 3 + 120

H 6 = 64x 6 480x 4 + 720x 2 120

H 2 = 4x 2 2

2 n+1

H n+1 (x)

2 n+1

2x H n (x)

2 n+1

2n H n1 (x)

2

=

n+1

β n = 0 γ n = n

2

¯

¯

H n+1 (x) = (x 0) H n (x) n La n1 (x).

¯

2

He n (x)

ω(x) =

2π exp x 2

1

2

x

He n+1 (x) = xHe n (x) He n1 (x),

He 0 ( x ) = 1 He 1 ( x ) = x •

He 0 (x) = 1 He 1 (x) = x

He 0 = 1

He 1 = x

He

He 3

= x 4 6x 2 + 3

2

=

x 2 1

=

x 3 3x

He 4

= x 5 10x 3 + 15

He 5

He 6 = x 6 15x 4 + 45x 2 15

f ( x ) f ( x ) [ a, b ] { x 0

f (x)

f (x)

[a, b] {x 0 , x 1 , ··· , x n }

b

a

f (x)dx

=

n

i=0

w i f(x i ),

w i x i

w(x) = 1

x [a, b] {t 1 , t 2 , ··· , t n } n1

F(x) =

n

i=1

(x t i ).

F (x)/(x t i ) n 1

lim

xt k

F(x)

x t

k

= F (t k )

= 0.

n 1

l k (x) =

F(x)

(x x k )F (x k ) ,

l k (x) = δ jk ,

{y 1

, y n }

n

L n (x) =

n

k=1

y k l k (x),

L n (x) n 1

L n (x j ) =

n

k=1

y k δ k (x) = y j ,

j = 1, 2, · · · , n.

n 1

(x i , y i ) ,

i = 1, 2, · · · , n,

L n (x) f (x) [a, b] x i [a, b] x i 2n 1 n ω i x i

f (x) [a, b]

I

= b f (x)dx ω 1 f(x 1 ) + ω 2 f(x 2 ).

a

x 1 , x 2 , ω 1 ω 2 f(x) = a 0 + a 1 x + a 2 x 2 + a 3 x 3 ,

n

I = b

a

f (x)dx ω 1 f(x 1 ) + ω 2 f(x 2 ) + ··· + ω n f(x n ).

n f (t) [1, 1] x [a, b]

x [1, 1] t [1, 1]

[a, b] [1, 1].

x = mt + c x = a x = b t = 1 t = 1

x = b a t + b + a

2

2

,

I = b f (x)dx =

a

1

1 f b a t + b + a b a

2

2

2

dt.

f (t)

I n

p I n p

2n 1 n

2n 2n

P n (x)

[a, b]

I =

b

a

f (x)w(x)dx,

w(x) [a, b].

a x 1 < x 2 < ··· < x n b, n

[a, b].

f (x) n x k , k = 1, 2, · · · , n,

I(f)

=

=

=

b

f (x)w(x)dx

a

b

a

n

k=1

n

k=1

P(x) (x x k

)P (x k ) + R n1 (c) w(x)dx

1

P

(x i )

b

a

P(x) x x

k

w(x)dx   f(x i )

+

b

a

R n1 w(x)dx.

I(f )

ω k ,

I(f) =

b

a

f (x)w(x)dx =

n

k=1

f(x k )ω k + E n (f ),

k = 1, 2, · · · , n,

ω k =

1

P

(x k )

b

a

P(x) x x

k w(x)dx.

E n (f) =

b

a

R n1 w(x)dx.

2n 1.

Le n (x)

w(x) = 1 [1, 1]

n

1

1

f (x)dx =

ω i f(x i ) + R n ,

i=1

R n =

(2n 2 + 1)[(2n)!] (n!) 3 f 2n (ξ), 1 < ξ < 1.

n+1

4

n x i

i ω i R n

2n.

x i

Le n (x),

2

(1 x

2

i

)[Le n (x i )] 2 .

[a, b]

ω i =

n = 3

x 1 , x 2 x 3 Le 3 (x)

Le 3 (x) =

2 1 (5x 3 3x).

x 1 = 3 ,

5

x 2 = 0

x 3 = 3 5 .

ω 1 = 5

9 ,

ω 2 = 8

9

ω 3 = 5

9 .

a

b

f (x)dx = 5 9 f 3 + 9 8 f (0) +

5

3

9 f 5

5

+ E 3

5, E 3 = 0 f (x) P 5 .

n

4n 2 .

β n = 0 γ n =

n

1

=

=

=

x i

w i

x i

w i

x i

w i